An Advanced Logarithmic Phase Mask for Extending Depth of Field of Hybrid Optical Systems - Nhu, Le Van; Nhue, Phan Nguyen; Hai, Le Hoang (Communications in Physics, 2017)
In this paper, an advanced logarithmic phase mask is proposed and its performance is investigated. The essential performance characteristics of phase masks are shown, including the defocused modulation transfer functions (MTF), integral area of the MTF, Hilbert space angle, non-axial Strehl ratio, and decoded images. The results have demonstrated that our phase mask is highly beneficial to extend the depth of field of hybrid optical systems. The advantages of the proposed phase mask in comparison to some other masks are also pointed out.